Criminalization of activism: historical, present, and future perspectives - Vegh Weis, Valeria (Routledge, 2022)
"Criminalization of Activism draws on a multiplicity of perspectives and case studies from the Global South and Global North to show how protest has been subject to processes of criminalisation over time. Bringing together a range of criminalisation themes into a single volume, compromising historical criminology, indigenous studies, gender studies, critical criminology, southern criminology, convict criminology and green criminology, it will be of great interest to scholars and students of criminology and sociology, as well as those involved in activism."--